2000
DOI: 10.14411/eje.2000.086
|View full text |Cite
|
Sign up to set email alerts
|

Life history of Adalia bipunctata (Coleoptera: Coccinellidae) in Japan

Abstract: Abstract. Adalia bipunctata is a well-known predaceous ladybird distributed in Europe, Central Asia and North America. This spe cies has not been recorded in Japan. Recently, we found this species in the Osaka Bay area in central Japan, and assume that it was imported with goods such as timber by ships. We studied the life history and the distribution in the Osaka Bay area since the initial discovery. The larvae and adults preyed on aphids (mainly, Periphyllus viridis) on trees such as Acer buergerianum and Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 5 publications
0
51
0
Order By: Relevance
“…Although A. bipunctata may be more polyphagous than C7 (Hodek, 1956;Blackman, 1967a, b), it is a narrower habitat generalist, occurring preferentially in arboreal habitats (Mills, 1979;Hon k & Hodek, 1996;Iperti, 1999, p. 335;Sakuratani et al, 2000;Sato et al, 2005;Eigenbrode et al, 2008). This stenotopy is associated with a morphological adaptation, a well developed anal disc in A. bipunctata larvae that is useful for adhering to plant surfaces.…”
Section: Habitat Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although A. bipunctata may be more polyphagous than C7 (Hodek, 1956;Blackman, 1967a, b), it is a narrower habitat generalist, occurring preferentially in arboreal habitats (Mills, 1979;Hon k & Hodek, 1996;Iperti, 1999, p. 335;Sakuratani et al, 2000;Sato et al, 2005;Eigenbrode et al, 2008). This stenotopy is associated with a morphological adaptation, a well developed anal disc in A. bipunctata larvae that is useful for adhering to plant surfaces.…”
Section: Habitat Specificitymentioning
confidence: 99%
“…Krafsur et al, 2005) indicates its ecological flexibility, even if its distribution in the western USA was enhanced by additional releases following the invasion of Diuraphis noxia (Louda et al, 2003). The invasive success of C7 in North America contrasts with the inability of Adalia bipunctata to expand its distribution in Japan after its establishment near Osaka in 1994 (Sakuratani et al, 2000;Kajita et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was suggested that urban areas provide footholds for the range expansion of invasive or distribution-extending insects, including ladybird beetles, (Sakuratani et al, 2000;Brown et al, 2011), buprestid beetles (Poland & McCullough, 2006), longicorn beetles (Dodds & Orwig, 2011), butterfl ies (Itô, 2001), cicadas (Takakura & Yamazaki, 2007;Moriyama & Numata, 2011), ants (Silverman & Brightwell, 2008) and mosquitoes (Romi et al, 2006;Caminade et al, 2012;Li et al, 2014), worldwide. It is evident that these insects increase and extend their distributions by using the physical structures, climate and food available in urban green spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Maredia et al, 1992;Lamana and Miller, 1996;Brown and Miller, 1998;Sakuratani et al, 2000;Wright and DeVries, 2000;Burkness et al, 2001), and they are often engaged in intraguild predation; e.g. larvae occasionally consume eggs, larvae and pupae of other species (Yasuda and Shinya, 1997;Cottrell and Yeargan, 1998;Sakuratani et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the survival and development of Harmonia axyridis Pallas are not adversely affected after consuming other species of ladybird (Yasuda and Ohnuma, 1999;Cottrell, 2004;Sato and Dixon, 2004). In addition, in the field, larvae of H. axyridis frequently consume eggs, larvae and pupae of other species (Yasuda and Shinya, 1997;Sakuratani et al, 2000), such as Propylea japonica (Sato, 2001). Therefore, H. axyridis is likely to be well adapted for intraguild predation (Sato et al, 2003;Sato and Dixon, 2004) and is a top predator among ladybirds (Dixon, 2000).…”
Section: Introductionmentioning
confidence: 99%